THE EFFECTIVENESS OF THE PROBLEM BASED LEARNING AND SOCIAL SKILLS LEARNING MODEL ON THE CRITICAL THINKING ABILITY OF GRADE V STUDENTS OF SDN 101901 LUBUK PAKAM: Efektivitas Model Pembelajaran Problem Based Learning Dan Keterampilan Sosial Terhadap Kemampuan Berpikir Kritis Siswa Kelas V SDN 101901 Lubuk Pakam - Yustika Adelina; Maximus Gorky Sembiring; Arif Rahman; Syahril Syahril (SOSIOEDUKASI, 2025)
This study aims to analyze the effectiveness of the Problem Based Learning (PBL) learning model and social skills on the critical thinking skills of grade V students of SDN 101901 Lubuk Pakam in Mathematics subjects. The research method used was a quasi-experiment with a 2x2 factorial design, involving 44 students who were divided into an experimental group (using PBL) and a control group (using an expository model). Data was collected through critical thinking ability tests and social skills observations, then analyzed using the two-path ANOVA test. The results of the study showed that: (1) The PBL model was effective in improving the critical thinking skills of students, both those who had high and low social skills, with the highest average score in the PBL group and high social skills (83.00). (2) The expository model is also influential, but it is more effective in students with high social skills (80.50) than in low (68.93). (3) There is a significant interaction between learning models and social skills in influencing critical thinking skills (p < 0.05). The implications of this study emphasize the importance of applying the PBL model to develop critical thinking skills, especially when supported by adequate social skills. Teachers are advised to design collaborative learning that not only focuses on problem-solving, but also trains students' social skills. These findings contribute to the development of Mathematics learning strategies in primary schools, especially in the face of the demands of 21st century skills.